2004
DOI: 10.1111/j.1445-1433.2004.02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital coronary artery fistulas: clinical considerations and surgical treatment

Abstract: Early surgical treatment for coronary artery fistulas is safe and effective. The risk of operative correction appears to be considerably less than the potential for development of serious and potentially fatal complications, even in asymptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 31 publications
0
48
0
2
Order By: Relevance
“…The majority of adult patients is to symptoms and usually must be treated surgically or by hemodynamic embolization with disposable balloon. Sternotomy and open heart ligation represent a more common option, sometimes using extracorporeal circulation support in more complex fistulous tracts [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of adult patients is to symptoms and usually must be treated surgically or by hemodynamic embolization with disposable balloon. Sternotomy and open heart ligation represent a more common option, sometimes using extracorporeal circulation support in more complex fistulous tracts [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The main referrals for surgical correction are the symptomatic cases, especially heart failure or myocardial ischemia. A previous criterion for the operation is in the presence of shunt (pulmonary blood/ systemic blood -Qp/Qs >2.0) and hemodynamic changes with heart insufficiency symptoms [1,3].…”
Section: Fig 2 -Preoperative and Postoperative Coronariography Of Comentioning
confidence: 99%
“…In acquired CAF, fistula formation have been associated with an increased expression of some growth factors such as vascular endothelial growth factor, which has the most important role in angiogenesis and vascular migration (11) . The incidence of symptoms and complications increases with age, particularly after the age of 20 (12,13) . The most frequent symptoms of CAF are dyspnea at rest or on exertion, fatigue, and angina (1,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have indicated that intracardiac closure of the distal end of CAFs under CPB reduces the likelihood of residual or recurrent fistulas. 12) On the other hand, transcatheter embolization of a CAF has been recently reported as an alternative to surgical therapy. 3,16,17) Although several complications such as T-wave inversion on an electrogram, embolization of the coil to the pulmonary artery, and transient arrhythmias were experienced in 30% of patients, 3,16) complete closure of CAVF was obtained in 78% to 82% of patients by transcatheter embolization.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have emphasized that the incidence of symptoms and complications increases with age, particularly after the age of 20. 11,12) A review of 187 patients has shown that symptoms and fistula-related complications occurred in 55% and 35% of patients over 20 years, respectively, but in 9% and 11% of those under 20 years old.…”
Section: Discussionmentioning
confidence: 99%